Lipid Analysis on Block Copolymer–containing Packaging Solution and Lens Care Regimens: A Randomized Clinical Trial. Issue 8 (August 2020) - Shows, Amanda; Redfern, Rachel L.; Sickenberger, Wolfgang; Fogt, Jennifer S.; Schulze, Marc; Lievens, Christopher; Szczotka-Flynn, Loretta; Schwarz, Stefan; Tichenor, Anna A.; Marx, Sebastian; Lemp-Hull, Jessie M.
Abstract : SIGNIFICANCE: Lotrafilcon B lenses packaged in and cared for with block copolymer–containing (polyoxyethylene-polyoxybutylene; EOBO) lens care solutions resulted in lower cholesterol extraction than each of the habitual silicone hydrogel lens/multipurpose solution (MPS) regimens tested. PURPOSE: This study aimed to compare the extracted cholesterol of lotrafilcon B lenses packaged in and cared for with EOBO-containing lens care solutions with the extracted cholesterol of habitual silicone hydrogel lenses cared for with MPS not containing EOBO. METHODS: In this prospective, randomized, observer-masked parallel study, habitual wearers of senofilcon C, senofilcon A, comfilcon A, and samfilcon A contact lenses using a non-EOBO MPS were randomized 1:1 to lotrafilcon B lenses packaged in and cared for with EOBO-containing solutions or to their habitual lenses and MPS. Subjects randomized to lotrafilcon B were further randomized to one of two EOBO-containing lens care solutions, OPTI-FREE PUREMOIST or CLEAR CARE PLUS with HydraGlyde (Alcon Laboratories, Inc., Fort Worth, TX). A subset of right eye lenses was collected after wear, and total cholesterol was extracted and measured using a fluorometric enzymatic assay. RESULTS: Of 143 lenses analyzed, 95 were from subjects randomized to their habitual lenses/MPS and 48 to lotrafilcon B + EOBO lenses plus CLEAR CARE PLUS with HydraGlyde or OPTI-FREE PUREMOIST. The mean amounts of cholesterol extracted from lotrafilcon B + EOBO lenses cared for with CLEAR CARE PLUS with HydraGlyde (0.28 ± 0.18 μg/lens) and OPTI-FREE PUREMOIST (0.28 ± 0.48 μg/lens) were significantly lower than those extracted from senofilcon C (4.18 ± 3.25 μg/lens), senofilcon A (2.19 ± 2.69 μg/lens), comfilcon A (2.17 ± 1.47 μg/lens), and samfilcon A (2.07 ± 1.48 μg/lens) lenses used with MPS ( P < .0001 each). CONCLUSIONS: Cholesterol sorption was significantly lower in wearers of lotrafilcon B lenses cared for with polyoxyethylene-polyoxybutylene–containing lens care solutions than in users of habitual silicone hydrogel lenses cared for with non–polyoxyethylene-polyoxybutylene MPS. Abstract : Supplemental digital content is available in the text.